Neural networks are a methodological basis of materials genome - Victor S Abrukov; Weiqiang Pang; Darya A Anufrieva (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
Materials Genome is an analytical and calculation tool that: contains all relationships between all variables of the object; allows to calculate of the values of one part of variables through others; allows to solve of direct and inverse problems; allows to predict of the characteristics of objects, which have not been investigated experimentally yet; allows to predict technology parameters to obtain an object with desired characteristics as well as allows to execute virtual experiment for conditions which cannot be organized or difficultly to organize. The paper presents the Neural Networks as a methodological Materials Genome basis. Possible areas of Neural Networks use are the development of new materials and their production.